2021
DOI: 10.12688/wellcomeopenres.16540.2
|View full text |Cite
|
Sign up to set email alerts
|

Early- and mid-career transitions to research leadership in Africa

Abstract: This article examines the early-and mid-career transition to research leadership in Africa. Much of the available African literature on research leadership indicate several challenges related to poor conceptualisations of career transitions and gaps in the availability of research training. Qualitative data were collected using individual interviews (n=24) and focus groups (n=27) to identify key transition points of early career researchers (ECRs) and mid-career researchers (MCRs) in selected African countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
(66 reference statements)
1
8
0
Order By: Relevance
“…Equally, the findings suggest that a well-led, well-structured consortium may still confer significant RCS opportunities even if funding is less than desirable: facilitating interactions between diverse groupings, role-modelling effective, engaging scientific leadership and providing quality postgraduate supervision, all stood out as RCS enablers that could be delivered at relatively minimal cost. Two recent studies, both also grounded within DELTAS Africa, similarly concluded that meaningful interactions (inclusive of those between junior and senior researchers and in the context of supervision) were essential to research and research leadership development 23 24. As with our study, Burgess and Chataway,23 further reported that DELTAS fellows regularly shared their experiences and/or resources gained through DELTAS Africa membership with institutional colleagues or visiting researchers from more resource poor groups.…”
Section: Discussionsupporting
confidence: 67%
“…Equally, the findings suggest that a well-led, well-structured consortium may still confer significant RCS opportunities even if funding is less than desirable: facilitating interactions between diverse groupings, role-modelling effective, engaging scientific leadership and providing quality postgraduate supervision, all stood out as RCS enablers that could be delivered at relatively minimal cost. Two recent studies, both also grounded within DELTAS Africa, similarly concluded that meaningful interactions (inclusive of those between junior and senior researchers and in the context of supervision) were essential to research and research leadership development 23 24. As with our study, Burgess and Chataway,23 further reported that DELTAS fellows regularly shared their experiences and/or resources gained through DELTAS Africa membership with institutional colleagues or visiting researchers from more resource poor groups.…”
Section: Discussionsupporting
confidence: 67%
“…Although this infrastructure appears to be directly applicable ‘only’ to the middle and low-middle income countries, it has been and is being largely adopted by the global north (for example, A Toroidal LHC ApparatuS diameter and Compact Muon Solenoid experiments at CERN’s Large Hadron Collider). Despite the differences in status, universities in both industrialized and developing countries often encounter inefficient coordination and restricted access to essential equipment and infrastructure 3 , 4 . The recent model implemented by the EUTOPIA European University , an alliance of 10 universities, presents an interesting example that demonstrates how coming together can be a means of mitigating inherent challenges within individual institutions regardless of their status and location.…”
Section: Coordinated and Co-managed Infrastructurementioning
confidence: 99%
“…as exemplified by the Future Seas Project; Nash et al, 2021) and leadership skills (including planning and management). Previous work has highlighted the value of experiential learning for women ECRs (Brasier et al, 2020) and the need for talent management to develop research leaders (Mtwisha et al, 2021). This can also benefit superiors.…”
Section: Ensure Early and Equitable Career Development Opportunities ...mentioning
confidence: 99%
“…The ECR stage is marked by a significant loss of women researchers (Holzinger et al, 2018;Gibson et al, 2020) particularly at the postdoctoral phase, when ECRs are applying for faculty positions or often when they realize that the demands on their time do not allow for a work-life balance (Shaw and Stanton, 2012). Attracting, retaining, developing, and promoting future women leaders is a priority that marine institutions and scientific communities cannot ignore (Mtwisha et al, 2021), especially if they wish to address gender inequality, bring in new perspectives and skills (Sobey et al, 2013;Nicholas et al, 2019;Brasier et al, 2020), increase research quality and diversity (Pannell et al, 2019;Kelly et al, 2021), deliver excellence in teaching and address ocean sustainability challenges (Keynejad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation